A Case of Retained Intra Orbital Foreign Body for 3 Months: Doi: 10.36351/pjo.v38i4.1422 - Junejo, Murtaza Sameen; Azeem, Teyyeb; Amer Yaqub, Muhammad (Pakistan Journal of Ophthalmology, 2022)
Orbital foreign bodies are not only difficult to detect but if retained for a long time can cause drastic complications such as orbital cellulitis, damage to extra ocular muscles and optic nerve injury. A prompt diagnosis and earlier removal can minimize the complication rate. Complications vary according to size, site and type of foreign body. Retained foreign bodies are very difficult to diagnose especially of wooden type even with advanced imaging techniques. We report a case of intra orbital wooden foreign body which was present for three months in a young boy.